Converting Unused Office Spaces in Kuala Lumpur: Potential Leisure Space - Zulkefli, Mohamad Nuruddin; Kozlowski, Marek (MAJ - Malaysia Architectural Journal, 2022)
For thousands of years through the history of humanity, humans will find activities to keep them entertained after completing their necessities, such as eating, working, and shopping. People taking up leisure activities in their life are happier and healthier. According to the Ministry of Tourism, Arts and Culture, family entertainment centres will create 3000 new jobs and benefit RM500 million to the national economy. In the meantime, the trend in Malaysian is that employees are overworked, which can lead to chronic stress and mental exhaustion among the workers. An office should cater to more than one specific function, and it should be flexibly readapted for other uses. However, there is no platform of leisure that complements the lifestyle of the urban setting in Malaysia. Hence, this study will highlight the issue of underused office spaces and suggests a framework of design guidelines on how to create a future entertainment centre in an existing office building. In this research, a case study will be used. This research will formulate design guidelines on how to develop a future entertainment centre in an office building context. This study is expected to contribute to the local authorities indicating how to conduct design guidelines aimed at repurposing an office building into an entertainment centre. This study will benefit potential stakeholders in advocating a leisure lifestyle in the urban environment. Lastly, this research's case study method only focuses on an unused office space in the KL Sentral area. Future research can explore other vacant buildings and possible spaces in different urban areas.